Respuesta :

Answer:   C. (-4, -2)

Step-by-step explanation:

First, eliminate one of the variables and solve for the remaining variable:

2x - 5y = 2      →    3(2x - 5y = 2)      →     6x - 15y = 6

3x + 2y = -16   →  -2(3x + 2y = -16)    →   -6x - 4y = 32

                                                                     -19y = 38

                                                                         y = -2


Next, replace "y" with -2 into either of the original equations to solve for x:

2x - 5y = 2

2x - 5(-2) = 2

2x + 10 = 2

2x         = -8

 x          = -4

                                       x = -4,  y = -2

Check:

Plug in the x- and y-values into the other original equation:

3x + 2y = -16

3(-4) + 2(-2) = -16

-12  +  -4     = -16

      -16         = -16   [tex]\checkmark[/tex]